Abundance of Soil Macrofauna in Various Land Cover Types in Balangan Regency, South Kalimantan Province - Wasis, Basuki; Sajadad, Dwi Hana (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
The presence of soil macrofauna has an important role in maintaining the stability of land ecosystems because they play a role in improving the physical, chemical and biological properties of soil that occur in the immobilization and humification processes. This research aims to analyze the abundance of soil macrofauna and the influence of vegetation types and the environment on the abundance of soil macrofauna in several land covers in Balangan Regency, South Kalimantan. Observations and soil sampling were carried out in a 20 m × 20 m plot using purposive sampling by making 5 subplots measuring 1 m × 1m. This research was carried out on four types of land, namely secondary forests, meranti forests, rubber plantations and empty land. Secondary forest is the only land that has significant differences in the abundance of macro fauna compared to other land uses. Secondary forests have the highest abundance of soil macrofauna, namely 80 individuals/m2, while the lowest is on vacant land at 0 individuals/m2. Secondary forest has the highest diversity, richness and evenness index compared to land cover. The high diversity and abundance of soil macrofauna is influenced by vegetation type, climatic factors (environmental temperature, humidity, light intensity) and edaphic factors (bulk weight, porosity, soil temperature, soil pH, organic C, respiration, litter wet weight, dry weight litter, and water content). Vacant land has the worst soil quality and the lowest abundance of macro fauna, so land reclamation on vacant land needs to be done as soon as possible to avoid soil damage. Key words: secondary forest, soil macro fauna, damaged soil, edaphic, climatic, vegetation